2017
DOI: 10.1016/j.scispo.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and prevention strategies for the musculoskeletal injuries in the paddle-tennis senior players

Abstract: Objective. To describe the incidence of musculoskeletal injuries in paddle-tennis senior players.Method. The sample was composed of 131 active paddle-tennis senior players (107 men / 24 women); with a mean age of 56.8±4.6 years [50 to 66 years] and 1.76±0.07 m, 81.3±16.44 kg and an average play time of 9.36±6.34 years. The 39.7% played at the right position; 79.4% over the medium level, 91.6% were right-hand and 62.6% were federated. Participants were asked about the injuries they had suffered during their pad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…Regarding injury locations, lower limbs seemed to be the most common location among padel players [ 10 , 68 ] with a close relationship to muscle overloading ( p < 0.001) and recurrent injuries ( p < 0.05) [ 11 ]. Other frequent injury locations, such as the lower back, knee, shoulder, hamstrings, calf, and plantar fascia have been reported [ 11 , 32 , 33 , 34 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding injury locations, lower limbs seemed to be the most common location among padel players [ 10 , 68 ] with a close relationship to muscle overloading ( p < 0.001) and recurrent injuries ( p < 0.05) [ 11 ]. Other frequent injury locations, such as the lower back, knee, shoulder, hamstrings, calf, and plantar fascia have been reported [ 11 , 32 , 33 , 34 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Castillo-Lozano et al [ 32 , 33 , 34 ] observed that age, body mass index, and laterality ( p < 0.05) were injury incidence determinants which could explain between 7.5% and 68.5% of injuries. These results were similar to those found by Garcia-Fernandez et al [ 11 ] who reported a higher injury rate in relation to age ( p < 0.05) and IMC increase ( p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…La tipología de los aspectos técnico-tácticos y temporales del pádel, a excepción del servicio, se caracteriza por estímulos y acciones de rápida ejecución con el objetivo de golpear la pelota al otro lado de la pista de manera precisa (Sánchez-Alcaraz, y Gómez-Mármol, 2015). Este conjunto de acciones se repiten a lo largo de partidos que se prologan más allá de la hora, por lo que los jugadores necesitan unos niveles de condición física que les permita ser eficaces de acuerdo a las demandas de la competición (Courel-Ibáñez, Sánchez-Alcaraz, y Cañas, 2015, 2017Muñoz et al, 2017;Torres-Luque, Ramírez, Cabello-Manrique, Nikolaidis, y Alvero-Cruz, 2015). Diferentes estudios han mostrado que las acciones de juego y los aspectos temporales del pádel pueden variar en función de la edad, el género de los deportistas o el tipo de entrenamiento, por lo que las exigencias físicas pueden ser diferentes según el perfil del practicante (Sánchez-Alcaraz, 2014a;2014b;Sánchez-Alcaraz, Sánchez-Pay, Gómez-Mármol, Molina-Saorín y Bazaco-Belmonte, 2017).…”
Section: Introductionunclassified
“…A lo largo de un partido de pádel un jugador realizar una gran cantidad de golpeos de manera unilateral (García Benítez, Courel-Ibáñez, Pérez-Bilbao, y Felipe, In press). Esta resistencia crónica a la fatiga provoca que el mayor índice de lesiones se produzca en el tren superior, especialmente en codos y hombros (Castillo-Lozano, 2017). Estudios Fecha recepción: 12-10-17.…”
Section: Introductionunclassified